Evaluating Personal Health Care and Health Promotion Web Sites - Lang, J. R.; Collen, A. (Methods of Information in Medicine, 2005)
Objective: An exemplary sample of web sites relevant to personal health care and health promotion was chosen and evaluated.Methods: Both quantitative and qualitative data were converged to assess and rank the sites on nine attributes.Results: The sites provided a definitive range of value and variety of presentations, health care and health promotion information, and services covering the virtual choices currently available to users of the Internet.Conclusion: Discussion focused on methodological approaches and issues of web site evaluation serving the public interest, health care, and health promotion.
Keywords: Health care; health promotion; methods; web site evaluation